Drug Trafficking - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2006)
Drug trafficking is a great peril, but also a reality of a modern world, especially because of its global character an unscrupulous ways of development and spreading throughout the planet. Therefore, there isn’t a single culture or society that does not have problems concerning this phenomenon and all of its effects and consequences. For better understanting of this problem, beside its consequences, a brief analysys was necessary regarding organized crime, conditions and ways of its constant and stubborn survival, the drug market itself, conceptional delimitation of phenomenon, drug abusers and reasons for existance of such need, farmacological characteristics of psyhoactive substances. Social reaction an usual doctrine in dealing with this problem, earlier researches, possibilities for eradication, and finally interaction between dealers and users are also a subject of this analysys, but with rather grim conlusion that the amount of „dirty money” tied to drug trafficking denies any real intention or possibility to stop or at least decrease such criminal operation. „Higher goals” of certain countries and agencies simply disregard their publicly proclamed objectives and endeavors of other services and usually other countries willing to fight this problem.